2022
DOI: 10.4103/jfmpc.jfmpc_812_22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge of ASHA workers regarding MCH services and practices followed by mothers – A field study

Abstract: A BSTRACT Background: Accredited social health activist (ASHA) workers act as a “bridge” between rural people and health service outlets and play a central role in achieving national health and population policy goals. According to the National Family Health Survey (NFHS) V (2019–2021) data, infant mortality rate (IMR) is still high in rural areas (32.4 per 1000 live births) in Punjab, compared to urban areas (20.1). Maternal mortality ratio (MMR) is also high (129 per l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…importance and initiation of breast milk . Kaur et al (2022) also reported that ASHA workers had good knowledge about (10) the importance of breast milk . In the present study, eighty percent of the workers had knowledge about exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 96%
“…importance and initiation of breast milk . Kaur et al (2022) also reported that ASHA workers had good knowledge about (10) the importance of breast milk . In the present study, eighty percent of the workers had knowledge about exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 96%